Ethno-medicinal Plants Used by Local Communities of Pokhara Metropolitan City of Kaski District, Western Nepal - Dhakal, Anisha; Paudel, Deepa; Neupane, Asmita; Gautam, Deepak (Kalika Journal of Multidisciplinary Studies, 2023)
In the diverse landscape of Pokhara Metropolitan City, Kaski district, Western Nepal, traditional medicine remains integral to the healthcare practices of many communities. This study presents a comprehensive exploration of the ethno medicinal value of locally available plants, emphasizing detailed insights into the research methodology employed. Data were collected from field observation, interview with local people, key informants, consultation with experts and secondary sources. Collected data were analyzed and presented well in table and charts. Data analysis involved a multi-faceted approach, including the systematic compilation of information gathered through interviews and field observations. The collected data were further organized and presented in tables and charts for comprehensive visualization. Plant specimens were meticulously collected, studied, and identified using standard literature and consultation with university professors. The results revealed a rich tapestry of ethno medicinal practices, showcasing 83 plant species distributed among 76 genera and 55 families, each playing a unique role in local healthcare. Trees emerged as the most prevalent life form, constituting 39.76% of the documented species. Noteworthy species included Ocimum tenuiflorum, Curcuma longa, and Citrus limon, with distinct medicinal applications The conservation and protection of these medicinal plants will further benefit in the prolonged sustainability of cultural as well as biological diversity.